In-vitro antioxidant, Xanthine oxidase-inhibitory and in-vivo Anti-inflammatory, analgesic, antipyretic activity of Onopordum acanthium - Sofiane Habibatni; Abdessalam Fatma Zohra; Hani Khalida; Sirajudheen Anwar; Iman Mansi; Nasser A Awadh Ali (International Journal of Phytomedicine, 2017)
Onopordum acanthium (Scotch thistle) belong to Asteraceae (Compositae). O. acanthium is a flowering biennial plant native to Europe and Western Asia with coarse spiny leaves 20-50 cm in width with conspicuous and spiny-winged stems. We have previously reported pro-apoptotic and cytotoxic effect of Onopordum acanthium crude extract against glioblastoma U-373 cells. The present study was designed to evaluate the cytotoxicity, antioxidant, xanthine oxidase inhibition, anti-inflammatory, analgesic, antipyretic activity of butanolic extract of Onopordum acanthium. Cytotoxicity of different solvent (methanolic, butanol, chloroform and petroleum ether) extract studied by brine shrimp lethality bioassay, total flavonoid and phenolic, antioxidant, xanthine oxidase inhibition activity was studied by in-vitro whereas anti- inflammation studied by carrageenan-induced paw edema model, antipyretic with 20 % brew yeast injection induced pyretic model, analgesic with 1 % acetic acid induced analgesic model investigated in in-vivo in wistar rats. Good antioxidant activity was found with IC50 = 134.4 µg/ml with considerable amount of total phenolic and flavonoid content. Xanthine oxidase inhibition effect was weak with IC50 = 572.9 µg/ml. Oral administration of O. Acanthium butanolic extract (OA) showed minimum lethality of brine shrimp nauplii henceforth OA butanolic phases was selected for further in-vivo studies. OA 200 and 400 mg/kg body weight decreased the oedema by 37.78 % and 40.52 %, respectively; standard aspirin 100 mg/kg decreased 42.62 % at 5th hour of Carrageenan injection. OA 200 and 400 mg/kg significantly decreased acetic acid-induced abdominal writhes when compared to standard aspirin. OA have shown dose and time dependent decrease in body temperature in yeast induced pyrexia, comparable to standard, aspirin. The present results demonstrate that OA has notable anti-inflammatory, antipyretic, analgesic activity related to presence of phenolic compounds as from literature it has been demonstrated that isolated compounds from aerial parts of Onopordum acanthium had strong activity in in-vitro assay.